The Role of Autonomy-Supportive Teaching Method in EFL Learning Contexts Worldwide - Kristian Wijaya (SAGA: Journal of English Language Teaching and Applied Linguistics, 2023)
One of the ultimate objectivities of education is to produce proficient, confident, and self-reliant learners possessing life-long learning characters. To comply with this educational aim, it is critically indispensable for worldwide EFL teachers to design a wide variety of student-oriented, encouraging, and meaningful learning activities sustaining the internalization of the autonomy-supportive teaching method. This present small-scale qualitative investigation was conducted through library study approach. Twenty current autonomy-supportive teaching literatures were selected to yield new enlightenment toward globalized ELT stakeholders’ beliefs concerning the critical importance of this student-centered learning mode in modern EFL areas. Based on the in-depth library analysis, the further utilization of the autonomy-supportive teaching method is highly recommended since EFL learners have transformed into more competent and self-reliant target language learners accompanied by the intensive learning supports addressed by language teachers. Some important suggestions are suggested for the future advancement of this current qualitative study.